2001
DOI: 10.1021/jm0004244
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Discovery of a Novel CCR1 Antagonist

Abstract: The CC chemokines may play an important role in the pathogenesis of chronic inflammatory diseases including rheumatoid arthritis, and their effects are thought to be mediated through CCR1 receptors. Several nonpeptide CCR1 receptor antagonists that showed high affinity for human CCR1 receptors have been identified; however, their effectiveness in animal models of inflammatory diseases has been scarcely demonstrated, probably due to species selectivity of the antagonists. To elucidate the pathophysiological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 15 publications
1
40
1
Order By: Relevance
“…Most notably, the basic nitrogen of the compounds is postulated to interact with a common acidic amino acid in TM7 of the receptor. Indeed, the quaternization of forerunners of the compound we describe here has been reported to increase their binding to the receptor (38). Although three of the analogous residues appear to interact with UCB 35625, we were unable to demonstrate a significant effect of the T86A mutation despite an apparent reduction in sensitivity to the compound.…”
Section: Mapping the Site Of Interaction For Ccr1-ucb 35625-contrasting
confidence: 59%
“…Most notably, the basic nitrogen of the compounds is postulated to interact with a common acidic amino acid in TM7 of the receptor. Indeed, the quaternization of forerunners of the compound we describe here has been reported to increase their binding to the receptor (38). Although three of the analogous residues appear to interact with UCB 35625, we were unable to demonstrate a significant effect of the T86A mutation despite an apparent reduction in sensitivity to the compound.…”
Section: Mapping the Site Of Interaction For Ccr1-ucb 35625-contrasting
confidence: 59%
“…The increased potency of BX 521 and BX 523 relative to BX 513 and BX 522 shows that both human and mouse CCR1 benefit from the increased basicity of a quaternary ammonium salt on the piperidine. This result is similar to that reported for the Banyu xanthenecarboxamide series following replacement of the piperidine nitrogen with a quaternary ammonium group (11).…”
Section: Figuresupporting
confidence: 89%
“…These findings provided the first clear evidence of the impact of mouse/human species variability of CCR1 on nonpeptide receptor antagonist potency. Recently, researchers from Banyu have reported that CCR1 inhibitors based upon a xanthenecarboxamide template also exhibit differential potencies on human and mouse CCR1s (11). These results demonstrate that the CCR1 mouse/human species variability also effects compounds from different template classes, a finding that may result from these inhibitors using a common antagonist binding site on CCR1.…”
mentioning
confidence: 92%
“…Control animals received vehicle alone. This compound has been reported to block both human and murine CCR1 (34). Two hours after the anti-CXCR2 or 30 min after the CCR1 antagonist administration, 1 ml of carrageenan (1%) was injected into the pouches, and 4 h later animals were sacrificed, exudates were collected, and samples were processed and analyzed as described.…”
Section: Effect Cxcr2 or Ccr1 Blockade On Chemokine Synthesis And Leumentioning
confidence: 99%